Demonstrating the potential of CO2 hydrate self-sealing in Svalbard, Arctic Norway. (October 2019) - Almenningen, Stian; Betlem, Peter; Hussain, Arif; Roy, Srikumar; Senger, Kim; Ersland, Geir
Abstract: Here we report the potential self-sealing properties of CO2 hydrate for the Longyearbyen CO2 Lab's shallow aquifer in Svalbard, Arctic Norway, through hydrate formation experiments. The experiments were conducted on a 9 cm long core plug of a fluvio-deltaic sandstone of the Barremian Helvetiafjellet Formation recovered from a fully-cored research well in Adventdalen in Svalbard at a depth of 187 m. CO2 injection into the brine-filled (1.0 wt.% NaCl) core plug was conducted at realistic reservoir conditions; the pore pressure was 20 bar and the temperature was 0.1 °C. Solid CO2 hydrate formed in the core plug after injecting 0.40 pore volumes (frac.) of CO2 and immediately reduced the apparent permeability to zero. A differential pressure across the core plug of 18 bar (200 bar/m) was sustained for 250 h without producing any CO2 from the core plug. This demonstrates the potential of CO2 hydrate formation as a secondary seal in settings with favorable CO2 hydrate formation conditions in or above the reservoir. The results further indicate that the self-sealing nature of CO2 hydrate should be considered while characterizing carbon sequestration reservoirs in both marine and permafrost-affected settings.